1647c Good practices to prevent occupational cancer from exposure to hazardous substances. (24th April 2018) - Fransman, Wouter
Abstract : In the EU, 1 00 000 to 1 50 000 people are diagnosed with cancer caused by exposure to carcinogenic substances during their work every year. This exposure causes a lot of personal injury and considerable social costs, also in comparison with other causes of death. Exposure to carcinogens is a major risk factor; good reason to address this by prevention at the source. This can be done by substitution of carcinogenic substances or processes, or by design of workplaces and tools in combination with frequent and careful use of dust-free tools and other good practices. The improvement potential is high and there are currently good initiatives in various sectors that create a healthy work environment. The currently available technological solutions offer great potential for improvement to reduce exposure. By better implementation, enforcement and information a lot of health profit will be gained. In order to work well, it is also important that workers are aware of the risks of carcinogens in their daily work. It is important to educate workers about the risks and the available solutions. For many of the control measures and good practices, the conditions are favourable, because there is a legal necessity: meeting the occupational exposure limit, contributing to good employment, funds are available and purchase costs are limited and cost reduction is possible on material costs and reduced cleaning costs. There are also a number of good initiatives and thus it seems possible to achieve a big effect. This presentation will give insight into various good practices and innovative technical solutions and methods in a variety of industries, which are currently available. When widely applied these good practices can heavily reduce work-related cancer in those sectors.